Top‐down HPLC–ESI‐MS characterization of rat gliadoralin A, a new member of the family of rat submandibular gland glutamine‐rich proteins and potential substrate of transglutaminase. Issue 17 (30th May 2013) - Cabras, Tiziana; Iavarone, Federica; Pirolli, Davide; Cristina De Rosa, Maria; Vitali, Alberto; Faa, Gavino; Cordaro, Massimo; Messana, Irene; Ekström, Jörgen; Castagnola, Massimo; Svec, Frantisek
<x xml:space="preserve">Abstract</x> During HPLC–ESI‐MS/MS analysis of rat submandibular saliva secreted under isoprenaline stimulation, a protein with an experimental [M+H]1+ = 10 544.24 m/z was detected (17.5 ± 0.7 min). The MS/MS fragmentation pattern, manually investigated, allowed establishing an internal sequence in agreement with a DNA‐derived sequence of an unknown rat protein coded D3Z9M3 (Swiss‐Prot). To match the experimental MS/MS fragmentation pattern and protein mass with theoretical data, the removal from the N terminus of the signal peptide and from the C terminus of three amino acid (a.a.) residues (Arg‐Ala‐Val) and the cyclization of the N‐terminal glutamine in pyroglutamic had to be supposed, resulting in a mature protein of 90 a.a. HPLC–ESI‐MS/MS of the trypsin digest ensured 100% sequence coverage. For the high glutamine content (34/90 = 37.8%) we propose to name this protein rat gliadoralin A 1–90. Low amounts of five different isoforms were sporadically detected, which did not significantly change their relative amounts after stimulation. Gliadoralin A is substrate for transglutaminase‐2, having Lys 60 and different Gln residues as major determinants for enzyme recognition. In silico investigation of superior structures evidenced that a small part of the protein adopts an α‐helical fold, whereas large segments are unfolded, suggesting an unordered conformation.